2019
DOI: 10.1002/14651858.cd008669.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy for periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis syndrome (PFAPA)

Abstract: Background Periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) syndrome is a rare clinical syndrome of unknown cause usually identified in children. Tonsillectomy is considered a potential treatment option for this syndrome. This is an update of a Cochrane Review first published in 2010 and previously updated in 2014. Objectives To assess the e ectiveness and safety of tonsillectomy (with or without adenoidectomy) compared with non-surgical treatment in the management of children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
(12 reference statements)
0
22
0
4
Order By: Relevance
“…Tonsillectomy has been reported to prevent recurrences and while this may be effective for patients with PFAPA, it is not without risk [26][27][28]. Although two small randomized control trials [26,27] suggested that patients with PFAPA have less fever and less severe episodes after tonsillectomy compared to those receiving no surgery, a Cochrane review [28] concluded that this evidence is of moderate quality (meaning that further research is likely to have an important impact on our confidence in the estimate of effect) due to the small numbers of patients in the studies and concerns about the generalizability of the results. Moreover, the number of patients randomly allocated to surgery was too small to detect potentially important complications.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillectomy has been reported to prevent recurrences and while this may be effective for patients with PFAPA, it is not without risk [26][27][28]. Although two small randomized control trials [26,27] suggested that patients with PFAPA have less fever and less severe episodes after tonsillectomy compared to those receiving no surgery, a Cochrane review [28] concluded that this evidence is of moderate quality (meaning that further research is likely to have an important impact on our confidence in the estimate of effect) due to the small numbers of patients in the studies and concerns about the generalizability of the results. Moreover, the number of patients randomly allocated to surgery was too small to detect potentially important complications.…”
Section: Discussionmentioning
confidence: 99%
“…85,86 In 2014, a Cochrane review compared these articles, being the only 2 randomly controlled trials applicable, and found a significant beneficial effect of tonsillectomy versus no surgery on both immediate and complete symptom resolution (number needed to treat to benefit = 2) and a substantial reduction in the frequency and severity (length of episode) of any further symptoms experienced. 87 Tonsillectomy may be considered per the frequency of illness, the severity of infection, and the child’s response to medical management.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Its association with some systemic diseases such as Behçet's disease, cyclic neutropenia, celiac disease, periodic fever, adenitis, pharyngitis and aphthae (PFA-PA) syndrome, oral and genital ulcers with inflamed cartilage (MAGIC) syndrome, Sweet's syndrome, Reiter's disease or some immunodeficiencies should be taken into account. [21][22][23] RAS is of unknown origin, and specific treatment is therefore not available; therapeutic measures are basically aimed at minimizing symptoms and preventing recurrences. The choice of topical or systemic treatment depends on symptom severity, lesion size and number and on the frequency of recurrent episodes.…”
Section: Introductionmentioning
confidence: 99%